2017
DOI: 10.1155/2017/4137563
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Granzymes A and B inEscherichia coliPeritonitis and Sepsis

Abstract: Escherichia (E.) coli is the most common causative pathogen in peritonitis, the second most common cause of sepsis. Granzymes (gzms) are serine proteases traditionally implicated in cytotoxicity and, more recently, in the inflammatory response. We here sought to investigate the role of gzms in the host response to E. coli-induced peritonitis and sepsis in vivo. For this purpose, we used a murine model of E. coli intraperitoneal infection, resembling the clinical condition commonly associated with septic perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…In addition, CLP sepsis shows a high degree of similarity with the progression of human sepsis, displaying both the hyper- and hypo-inflammatory responses characteristic of human sepsis 32 , 33 . It has been shown previously that GzmA might contribute to septic shock induced by LPS 16 , 17 or to sepsis induced by single bacterial agents like the mouse pathogen B. microti 18 , S. pneumoniae 19 or E. coli 34 . However, the role of GzmA in abdominal polymicrobial sepsis had so far not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CLP sepsis shows a high degree of similarity with the progression of human sepsis, displaying both the hyper- and hypo-inflammatory responses characteristic of human sepsis 32 , 33 . It has been shown previously that GzmA might contribute to septic shock induced by LPS 16 , 17 or to sepsis induced by single bacterial agents like the mouse pathogen B. microti 18 , S. pneumoniae 19 or E. coli 34 . However, the role of GzmA in abdominal polymicrobial sepsis had so far not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…This is a new finding, which somewhat contradicts the known increased tumor/nontumor ratios for total amount of the two SFs [1] , [8] , [11] , [13] . Although Mw-shifted-HNRNPA1 or -SRSF1 inducing clinical status has rarely been studied, a granzyme (cytotoxic protease upregulated during bacterial infection and released by immune cells)-treated cell line model showed cleavage of HNRNPA1 as a mobility shift (faster migration) on an immunoblot, which is fairly consistent with the relative levels of LMw-HNRNPA1 in PNPE and TBPE [6] , [30] ; these types of PEs are associated with bacterial infection and immune cell activation [21] , [23] , [24] , [25] , [26] .…”
Section: Discussionmentioning
confidence: 67%
“…The activity of Gzms during infectious diseases and sepsis seems to differ between anatomical site as well as the type of pathogen involved. For instance, a study showed that there was low level of GzmA in peritoneal lavage fluid of healthy mice while this level increased overtime during sepsis induced by E. coli (43). On the other hand, in a pneumonia-induced sepsis using a gram positive bacteria (Streptococcus pneumoniae) model the opposite was found (42).…”
Section: Granzymes Are Elevated In Patients Suffering From Sepsismentioning
confidence: 99%